The Pottery of Mount Zion: An Overview from Islamic to Iron Age Periods - Schöpf, Friederike (Archäologischer Anzeiger, 2021)
The excavation of the southwestern slope of Mt. Zion during the years 2016–2019, conducted by the DEI, revealed pottery finds dating from Iron Age II to the Ottoman period. Altogether, three different areas were excavated. This article aims to present and discuss the pottery corpus found during the excavation campaigns. The chronological and typological analysis of these finds helps to integrate the excavation into the history of Jerusalem. Moreover, they can shed new light on the eventful history of Mt. Zion and represent the use of the area in the different periods.